(untitled) (@limentech, Ciencia y Tecnología Alimentaria, 2022)
Ultrasound has a wide range of applications in the Food Industry, especially for the meat line and its effects on quality and technological properties such as texture, water retention, color, curing, marinating, cooking performance, freezing, thawing and microbial inhibition. In this work we studied, the effect of the Application of ultrasonic fields in Meat Emulsions and its effect on color and texture, using colorimetry and texture profile analysis to determine, strength, elasticity, gumminess, chewability, cohesiveness and adhesiveness. The analyzed samples were obtained from a Premium type meat emulsion elaborated in the Centro de Attention al Sector Agropecuario Sena Regional Santander, different times of application of ultrasound were used and a singleconstant of acoustic wave of 40 khz, they were followed for 3 months to study their texture aand colorimetry profile. It is concluded that ultrasound is a useful tool in the meat emulsion industry, decreasing its texture and improving its chewiness and gumminess.